Better corporate governance leads to better performance: evidence from Asian countries - Asghar, Muhammad Jam e Kausar Ali; Anwar, Zeshan; Usman, Muhammad; Khan, Hamad (Publishing House of Wroclaw University of Economics and Business, 2021)
The most contentious element in debate regarding corporate governance is the association of corporate governance (CG) with firm performance. This research employed the 2SLS regression model on a panel data, collected from 24 Asian multinationals from 2006 to 2015. The firm performance was measured in two ways; accounting measure (ROA and sales growth) and market measure (Tobin’s Q). The outcomes demonstrate that quality of corporate governance (QCG) index has a significant association in enhancing the performance of firms in Asian economies. Furthermore, these results also indicate that explicit corporate governance variables such as board independence, audit committee independence, ownership concentration and CEO duality, also have significant association with the performance of companies in Asian countries which is in accordance with the agency theory
Argumenta Oeconomica, 2021, Nr 1 (46), s. 183-204